(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
In this paper, a magnetically coupled piezoelectric energy harvester is proposed. A dual-mass system is fitted with a bluff body to harvest vortex-induced vibration (VIV) from a fluid flow in an open channel setup. Vortices formation behind the bluff body leads to utilizing vibration-based energy harvesting. Increasing the water velocity increases the overall output voltage and until a maximum at the natural frequency of the system when synchronization phenomena is observed. Broadband energy harvester is achieved by attaching magnets on the bluff body and is useful for increasing the harvestable range of variable flows. While conventional narrowband energy harvesters are still more superior when near to the natural frequency, the magnet coupling broadens the synchronization range of the harvesters by 35%. This proposed design made from 3D printed components can be used as a framework for compact energy harvesters and placed in multiple arrays inside pipelines to power wireless sensing devices.